Effects of Swaddling During Bottle Feeding in Preterm Infants. (2nd April 2023) - Smith, Allison P.; Sweeney, Jane K.; Ross, Erin Sundseth; Blackburn, Susan
Abstract : Background: Preterm infants have immature oral feeding skills, affecting length of hospital stay and long-term feeding outcomes. Swaddling has positive effects on pain and stress responses, state regulation, and physiological stability in preterm infants in the neonatal intensive care unit (NICU). Swaddling during bottle feeding may support preterm infant behavioral organization and oral feeding skills. Swaddling is used inconsistently during feeding in the NICU and has not been critically examined for effects on bottle feeding performance in preterm infants. Purpose: To examine the effects of swaddling on bottle feeding quality and efficiency in preterm infants. Methods: A convenience sample of 30 infants born before 34 weeks of gestation was selected in an urban level IV NICU. Using an experimental, randomized crossover design, each infant was swaddled for one feeding and unswaddled for one feeding. Feeding efficiency was measured by rate and volume consumed. Feeding quality was examined by the Early Feeding Skills Assessment and frequency of physiological changes. Data were analyzed using dependent t tests and Wilcoxon signed rank test. Results: When swaddled, participants demonstrated significantly better scores on all related subtests of the Early Feeding Skills Assessment ( P ≤ .001). Infants demonstrated no difference in frequency of bradycardia or oxygen desaturations greater than 4 seconds. No significant differences were found in feeding efficiency outcomes. Implications for Practice and Research: Swaddling can be used in the NICU to improve bottle feeding quality in preterm infants. Future investigation is needed on long-term effects of swaddling during bottle feeding on feeding performance, weight gain, and length of stay.